Motor unit number estimations are smaller in children with type 1 diabetes mellitus: A case–cohort study. Issue 4 (5th August 2014) - Toth, Cory; Hebert, Valerie; Gougeon, Claire; Virtanen, Heidi; Mah, Jean K.; Pacaud, Daniele
ABSTRACT Introduction: We studied the potential for motor unit number estimation (MUNE) to detect subclinical changes in motor unit numbers in children with type 1 diabetes mellitus (DM). Methods: Blinded observers performed clinical assessment, electrophysiology, and multipoint MUNE of the extensor digitorum brevis muscle in children with DM for ≥5 years and age‐matched healthy controls. Results: For 51 DM subjects, the disease duration was 9.1 ± 2.6 years. Subjects with DM and healthy controls (n = 21) had similar demographics. There were no clinical symptoms or signs of peripheral neuropathy in any subject, nor differences in standard electrophysiology between cohorts. Estimated motor unit numbers were decreased significantly in children with DM (224 ± 87 vs. 274 ± 101, P = 0.036). Conclusion: Despite the absence of clinical or standard electrophysiological differences from normal control subjects, MUNE can detect a small significant difference in children with DM, suggesting that motor unit loss begins early and subclinically in the disease. Muscle Nerve 50: 593–598, 2014